2019
DOI: 10.1111/nyas.14043
|View full text |Cite
|
Sign up to set email alerts
|

Methadone's effects on pentylenetetrazole‐induced seizure threshold in mice: NMDA/opioid receptors and nitric oxide signaling

Abstract: Methadone is a synthetic opioid used to treat opiate withdrawal and addiction. Studies have demonstrated the impact of methadone on seizure susceptibility. This study investigated the modulatory impacts of acute and subchronic (three times daily for 5 days) intraperitoneal methadone treatment on pentylenetetrazole‐induced clonic seizure threshold (CST) in mice, as well as the involvement of the nitric oxide, N‐methyl‐d‐aspartate (NMDA), and µ‐opioid pathways. Acute administration of different doses of methadon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…The role that opioid receptors play in seizures is complex. Low doses of morphine have an anticonvulsant impact, although high doses have the opposite effect 25–29 . Opioids worsen, and antagonists prevent absence‐like seizures, 30,31 and a polymorphism in the N‐terminal μ opioid receptor in humans confers genetic susceptibility to idiopathic absence epilepsy 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role that opioid receptors play in seizures is complex. Low doses of morphine have an anticonvulsant impact, although high doses have the opposite effect 25–29 . Opioids worsen, and antagonists prevent absence‐like seizures, 30,31 and a polymorphism in the N‐terminal μ opioid receptor in humans confers genetic susceptibility to idiopathic absence epilepsy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Opioids worsen, and antagonists prevent absence‐like seizures, 30,31 and a polymorphism in the N‐terminal μ opioid receptor in humans confers genetic susceptibility to idiopathic absence epilepsy 32 . Low and ultra‐low doses of NTX potentiate the anticonvulsive effect of morphine and cannabinoids, 33–36 and NTX reverses the convulsive effect of acute methadone injections 29 . However, other studies indicate that NTX can potentiate seizures 37–39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies showed that acute administration of methadone could substantially reduce the seizure threshold. NMDA and μ-opioid receptors may be involved in methadone's convulsive activity in the acute methadone overdose [25].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies showed that acute administration of methadone could substantially reduce the seizure threshold. NMDA and µopioid receptors may be involved in methadone's convulsive activity in the acute methadone overdose [25].…”
Section: Discussionmentioning
confidence: 99%